Preparation method of bipolar electrode

The preparation of bipolar electrodes through dry mixing and rolling technology solves the difficulties in the alignment of the lithium battery electrodes and current extraction method, achieves higher battery capacity and output voltage, and reduces safety risks.

CN119695059APending Publication Date: 2025-03-25JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411824268.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

There are difficulties in the current extraction method of the electrode and the electrode alignment control, which affects the battery capacity, output voltage and safety.

Method used

The bipolar electrode is prepared by dry mixing and rolling technology. The multi-layer current collector formed by composite of multiple metal layers is used as the basis to adhere the positive electrode and negative electrode active material layers respectively to ensure the compaction density and bonding effect of the different polar active material layers on both sides.

Benefits of technology

The battery capacity and output voltage are improved, the bond strength and conductivity stability of the electrode layer and current collector are enhanced, safety risks are reduced, and material management and production processes are simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005183841990000161
    Figure BDA0005183841990000161
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a preparation method of a bipolar electrode. The preparation method comprises the following steps: firstly, preparing a multi-layer current collector formed by compounding a plurality of metal layers, then coating two sides of the multi-layer current collector with a conductive adhesive, respectively adhering two sides of the multi-layer current collector with a positive active material layer and a negative active material layer, and baking to obtain the bipolar electrode. The bipolar electrode prepared by the invention can effectively improve the battery capacity, the battery energy density and the high-voltage output, so that the bipolar electrode has a wide application prospect in the technical field of batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and in particular to a method for preparing a bipolar electrode. Background Art

[0002] The production method of lithium batteries is to alternately combine positive pole pieces, separators, and negative pole pieces together by winding or stacking to form a roll core. In order to increase the capacity and output voltage of the battery cell and reduce safety risks, the alignment and coating margin of the pole pieces and separators become difficult points in process control and have a great impact on the entire life cycle of lithium batteries; the current extraction method of the electrode also affects the application scenario of the battery. Existing researchers have proposed a bipolar pole piece, which is characterized by coating positive and negative active material layers on both sides of the current collector, thereby combining the positive and negative electrodes into a pole piece. This bipolar pole piece can effectively increase the battery capacity and achieve high voltage output; and in the prior art, the current collector of this bipolar pole piece is a multilayer current collector in the form of a polymer film metallized on both sides, which can further increase the battery energy density.

[0003] In order to overcome the defects of the prior art, the present invention provides a method for preparing a bipolar electrode. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a bipolar electrode to solve the problems in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A bipolar electrode comprises a multi-layer current collector formed by a composite of multiple metal layers; a positive electrode active material layer and a negative electrode active material layer of target compaction density are obtained by dry mixing and roller pressing respectively, the positive electrode active material layer is adhered to the positive electrode side of the multi-layer current collector, and the negative electrode active material layer is adhered to the negative electrode side of the multi-layer current collector.

[0007] More optimally, the metal layer is any one of a copper layer and an aluminum layer.

[0008] More optimally, an insulating layer or a carbon layer is sandwiched between the multiple metal layers.

[0009] More optimally, the compaction density of the positive electrode active material layer is 3.5-4.0 g / cm 3 The compaction density of the negative electrode active material layer is 1.7-2.0g / cm 3 .

[0010] More optimally, the thickness of the positive electrode active material layer is 300-400 μm; the thickness of the metal layer is 1.0-1.5 μm; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 2-10 mm and a depth of 0.1-1 mm.

[0011] More optimally, the preparation process of the positive electrode active material layer is as follows: nickel cobalt manganese, carbon nanotubes and conductive carbon black are mixed, and ball milled to obtain a positive electrode preparatory material; the positive electrode preparatory material and polytetrafluoroethylene are mixed, and high-speed shear fiberization is performed to obtain a positive electrode mixture; the positive electrode mixture is rolled to obtain a positive electrode active material layer; positive electrode high-speed shear fiberization parameters: the fiberization speed is 30000-50000rpm / min, and the fiberization time is 2-10min; positive electrode rolling parameters: the positive electrode mixture is first preheated at 80-120°C for 10-60min, and then rolled, and the rolling pressure is 8-20t;

[0012] The preparation process of the negative electrode active material layer is as follows: graphite and conductive carbon black are mixed, and the mixture is ball-milled to obtain a negative electrode preparatory material; the negative electrode preparatory material and polytetrafluoroethylene are mixed, and the mixture is subjected to high-speed shear fiberization to obtain a negative electrode mixture; the negative electrode mixture is rolled to obtain a negative electrode active material layer; negative electrode high-speed shear fiberization parameters: the fiberization speed is 30000-50000rpm / min, and the fiberization time is 2-10min; negative electrode rolling parameters: the negative electrode mixture is first preheated at 50-100°C for 10-60min, and then rolled, and the rolling pressure is 6-12t.

[0013] More optimally, the positive electrode preparation material consists of 98.5wt% nickel cobalt manganese, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture consists of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene; the negative electrode preparation material consists of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture consists of 99wt% negative electrode preparation material and 1wt% polytetrafluoroethylene.

[0014] The preparation method of the bipolar electrode comprises the following steps: dry-mixing the positive electrode raw material and the negative electrode raw material, respectively, and performing fiberization and roller pressing to obtain the positive electrode active material layer and the negative electrode active material layer; then coating the conductive glue on both sides of the multilayer current collector, respectively, and then bonding the positive electrode active material layer and the negative electrode active material layer on both sides, respectively, to obtain the bipolar electrode.

[0015] More optimally, the preparation process of the conductive adhesive is as follows: polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer are mixed, and the mixture is stirred and reacted at 150-160°C for 2-3 hours in a vacuum to obtain a modified polyolefin resin; the modified polyolefin resin, paraffin wax and conductive agent graphene are mixed, and the mixture is stirred at a speed of 1200-1300 rpm for 1.5-2.0 hours to obtain a conductive adhesive.

[0016] More optimally, the reaction mass ratio of polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer is (20-25):3:20; the reaction mass ratio of modified polyolefin resin, paraffin and conductive agent graphene is (10-12):1:10.

[0017] More optimally, the positive electrode active material layer is first bonded to the multi-layer current collector and then baked at 105-110°C for 10-15 min, and then the negative electrode active material layer is bonded to the multi-layer current collector and baked at 100-105°C for 10-15 min.

[0018] Beneficial effects of the present invention:

[0019] 1. This solution applies dry electrode technology to bipolar electrodes, rolls the active materials on the positive and negative sides respectively, and then composites the active material layer onto the current collector by transfer, which not only ensures the bonding strength and conductive stability between the active material layer and the current collector, but also meets the requirements of different compaction densities of active material layers of different polarities on both sides of the bipolar electrode. In addition, dry electrodes do not require solvents, and the gaps between particles are smaller, making it easier to achieve a higher compaction density.

[0020] 2. The bipolar current collector is composed of two metal layers, with conduction on both sides of the positive and negative electrodes. It can be used in solid-state batteries to achieve series connection of multiple battery cells and increase the battery output voltage. The two metal layers are composited with an insulating layer sandwiched between them (i.e., a multi-layer current collector), which can be applied to ordinary batteries. The positive and negative electrodes are insulated from each other, and the battery is equivalent to multiple battery cells connected in parallel. The beneficial effect is that there is only one electrode material when the battery is wound or stacked, which can greatly improve the alignment of the positive and negative electrodes and the diaphragm, while simplifying material management and production processes.

[0021] 3. Conventional electrode rolling is to roll the current collector coated with active material layers on both sides together. During the rolling process of thick electrodes, due to uneven force transmission, the surface compaction density of the active materials on both sides is usually greater than the compaction density of the inner layer, which will affect the transmission of electrons and lithium ions. In addition, for thick electrodes prepared with multi-layer current collectors, since the insulating layer in the middle of the multi-layer current collector is generally a high molecular polymer, its elongation is much greater than that of pure metal current collectors, which can easily lead to a large stress difference between the inner layer and the surface layer of the active material layer, causing cracking of the active material layer, affecting product quality. This solution can solve the above problems very well.

[0022] 4. Since the electrodes on both sides of the bipolar current collector are different, during the battery charging and discharging process, the opposite directions of lithium ion insertion and extraction will cause different expansion on both sides, especially when the negative electrode is fully charged, the negative electrode side expands more, causing the stress on both sides of the pole piece to be different, causing the pole piece to curl toward the positive electrode side on the opposite side, which will cause the battery to expand seriously, and also cause the negative electrode side to fit poorly with the positive electrode on the opposite side, resulting in lithium precipitation problems. After the negative electrode mixture is formed by roller pressing, it is embossed by an embossing roller. The surface of the embossing roller is provided with protrusions, so that pores or pit structures are left on the surface of the negative electrode active material layer after rolling. These pores or pit structures can be used to alleviate the expansion problem on the negative electrode side. Surface embossing of the negative electrode active material layer can be performed before the negative electrode active material layer is compounded with the current collector, reducing the impact on the positive electrode side and the current collector structure.

[0023] 5. In the bipolar electrode processing method, the dry material mass ratio of the conductive agent to the binder in the conductive glue is (0.3-1). The conductivity and the life of the pole piece are guaranteed by ensuring the bonding strength between the positive electrode active material layer, the negative electrode active material layer and the current collector, that is, the binder ratio. At the same time, the conductive agent ratio should not be too low. The binder usually has poor conductivity, and the conductive agent needs to be added to ensure the balance of the conductive agent performance. The conductive agent can be selected from one or more of carbon black, graphene, carbon nanotubes, graphite, graphene, and mesophase carbon microspheres. The binder is selected from one or more of polyacrylic acid, polyolefin, acrylate, and polyamino acid.

[0024] 6. In the bipolar electrode processing method, the positive electrode active material layer is first compounded with the current collector and then dried once, and then the negative electrode active material layer is compounded with the current collector and dried twice. The compaction density of the negative electrode active material layer is usually lower than that of the positive electrode, and it is more prone to powder loss than the positive electrode. The toughness of the positive electrode side is stronger, so the negative electrode active material layer is compounded with the current collector after compounding on the positive electrode side, reducing the number of times the negative electrode active material layer is rolled and reducing the risk of powder loss. In addition, the positive electrode active material layer needs to be dried once after being compounded with the current collector to avoid misalignment and shedding of the positive electrode and the current collector during winding. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Source of raw materials:

[0027] Carbon nanotubes, provided by Shandong Tanfeng New Materials Technology Co., Ltd., with a particle size of 10 μm; conductive carbon black, provided by Shanghai Haoren International Trade Co., Ltd., with a particle size of 23 nm; polytetrafluoroethylene, provided by Dongguan Hualixing Plastic Raw Materials Co., Ltd., model 350; graphite, provided by Lingshou Jiashuo Building Materials Processing Co., Ltd., with a particle size of 80 mesh; polypropylene, provided by Dongguan Jintai New Materials Technology Co., Ltd., model GH41; styrene-ethylene-butylene-styrene block copolymer, provided by Shanghai David New Materials Co., Ltd., model G1652MU; paraffin, provided by Shandong Zhengyu Chemical Technology Co., Ltd., with a density of 1.2 g / cm 3 ; Graphene, provided by Henan Wanying Refractory Materials Technology Co., Ltd., with a specification of 1000 mesh; artificial graphite, provided by Shijiazhuang Chen Gaoxin Materials Technology Co., Ltd., with a specification of 80 mesh; styrene-butadiene rubber, provided by Guangdong Dingxin Polymerization Technology Co., Ltd., model SEBS A1535HU; sodium carboxymethyl cellulose, provided by Jiangsu Jiujia Biotechnology Co., Ltd., with a molecular weight of 263.2.

[0028] Embodiment 1: A multilayer current collector is composed of an aluminum layer and a copper layer, without a base film, wherein the aluminum layer is the positive electrode side and the copper layer is the negative electrode side: Step 1: providing a copper plate and an aluminum plate; stacking the copper layer and the aluminum layer, and preheating them at 280° C. for 20 min; rolling the preheated copper layer and the aluminum layer for compounding, with a rolling pressure of 3000 t, a rolling speed of 1 m / s, and a rolling deformation of 40%, to obtain a multilayer current collector; wherein the thickness of the copper layer is 6 mm, and the thickness of the aluminum layer is 7 mm;

[0029] Step 2: Mix nickel-cobalt-manganese 811, carbon nanotubes and conductive carbon black, and ball-mill at a speed of 500 rpm for 2 hours to obtain a positive electrode preparatory material; mix the positive electrode preparatory material and polytetrafluoroethylene, and put the mixed mixture into a high shear machine for fiberization at a fiberization speed of 35000 rpm / min for a fiberization time of 5 minutes to obtain a positive electrode mixture; preheat the positive electrode mixture at a preheating temperature of 80°C for 40 minutes, and then enter a hot press roller machine for rolling at a rolling pressure of 20t to roll the positive electrode mixture to obtain a positive electrode active material layer; the compaction density of the positive electrode active material layer is 3.5g / cm 3 , with a thickness of 350μm; the positive electrode preparation material is composed of 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture is composed of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene;

[0030] The graphite and the conductive carbon black were mixed, and the mixture was ball-milled at a speed of 500 rpm for 2 hours to obtain a negative electrode preparatory material; the negative electrode preparatory material was mixed with polytetrafluoroethylene, and the mixed mixture was placed in a high shear machine for fiberization at a fiberization speed of 35000 rpm / min and a fiberization time of 5 minutes to obtain a negative electrode mixture; the negative electrode mixture was preheated at a preheating temperature of 60°C for 30 minutes, and then rolled in a hot press roller machine at a rolling pressure of 12 tons to obtain a negative electrode active material layer; the compaction density of the negative electrode active material layer was 1.7 g / cm 3 , with a thickness of 180μm; the contents of the components of the negative electrode mixture are: by mass fraction, 99wt% graphite, 1wt% conductive carbon black, and the balance is polytetrafluoroethylene; the negative electrode preparatory material is composed of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture is composed of 99wt% negative electrode preparatory material and 1wt% polytetrafluoroethylene; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 6mm and a depth of 0.7mm;

[0031] Step 3: Mix polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer, stir and react at 150°C for 2 hours to obtain a modified polyolefin resin; mix the modified polyolefin resin, paraffin wax and conductive agent graphene, stir at a speed of 1200 rpm for 1.5 hours to obtain a conductive adhesive; the reaction mass ratio of polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer is 20:3:20; the reaction mass ratio of modified polyolefin resin, paraffin wax and conductive agent graphene is 10:1:10;

[0032] The conductive glue was coated on both sides of the multilayer current collector respectively, and then the positive electrode active material layer was adhered to the positive electrode side and baked at 105°C for 15 minutes; then the negative electrode active material layer was adhered to the negative electrode side and baked at 100°C for 15 minutes to obtain a bipolar electrode; the thickness of the conductive glue was 1 μm.

[0033] Embodiment 2: The multilayer current collector is composed of an aluminum layer, a base film, and a copper layer; the base film is a carbon layer, the aluminum layer is the positive electrode side, and the copper layer is the negative electrode side: Step 1: Prepare an aluminum layer with a thickness of 1 μm on one side of a flexible carbon layer base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and prepare an aluminum layer with a thickness of 1 μm on the other side by a vapor deposition process to obtain a multilayer current collector;

[0034] Step 2: Mix nickel-cobalt-manganese 811, carbon nanotubes and conductive carbon black, and ball-mill at a speed of 500 rpm for 2 hours to obtain a positive electrode preparatory material; mix the positive electrode preparatory material and polytetrafluoroethylene, and put the mixed mixture into a high shear machine for fiberization at a fiberization speed of 35000 rpm / min for a fiberization time of 5 minutes to obtain a positive electrode mixture; preheat the positive electrode mixture at a preheating temperature of 80°C for 40 minutes, and then enter a hot press roller machine for rolling at a rolling pressure of 20t to roll the positive electrode mixture to obtain a positive electrode active material layer; the compaction density of the positive electrode active material layer is 3.5g / cm 3 , with a thickness of 350μm; the positive electrode preparation material is composed of 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture is composed of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene;

[0035] The graphite and the conductive carbon black were mixed, and the mixture was ball-milled at a speed of 500 rpm for 2 hours to obtain a negative electrode preparatory material; the negative electrode preparatory material was mixed with polytetrafluoroethylene, and the mixed mixture was placed in a high shear machine for fiberization at a fiberization speed of 35000 rpm / min and a fiberization time of 5 minutes to obtain a negative electrode mixture; the negative electrode mixture was preheated at a preheating temperature of 60°C for 30 minutes, and then rolled in a hot press roller machine at a rolling pressure of 12 tons to obtain a negative electrode active material layer; the compaction density of the negative electrode active material layer was 1.7 g / cm 3 , with a thickness of 180μm; the contents of the components of the negative electrode mixture are: by mass fraction, 99wt% graphite, 1wt% conductive carbon black, and the balance is polytetrafluoroethylene; the negative electrode preparatory material is composed of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture is composed of 99wt% negative electrode preparatory material and 1wt% polytetrafluoroethylene; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 6mm and a depth of 0.7mm;

[0036] Step 3: Mix polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer, stir and react at 150°C for 2 hours to obtain a modified polyolefin resin; mix the modified polyolefin resin, paraffin wax and conductive agent graphene, stir at a speed of 1200 rpm for 1.5 hours to obtain a conductive adhesive; the reaction mass ratio of polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer is 20:3:20; the reaction mass ratio of modified polyolefin resin, paraffin wax and conductive agent graphene is 10:1:10;

[0037] The conductive glue was coated on both sides of the multilayer current collector respectively, and then the positive electrode active material layer was adhered to the positive electrode side and baked at 105°C for 15 minutes; then the negative electrode active material layer was adhered to the positive electrode side and baked at 100°C for 15 minutes to obtain a bipolar electrode; the thickness of the conductive glue was 1 μm.

[0038] Embodiment 3: A multilayer current collector is composed of an aluminum layer, a base film, and a copper layer, and the base film is a PET base film: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and an aluminum layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0039] Step 2: Mix nickel-cobalt-manganese 811, carbon nanotubes and conductive carbon black, and ball-mill at a speed of 500 rpm for 2 hours to obtain a positive electrode preparatory material; mix the positive electrode preparatory material and polytetrafluoroethylene, and put the mixed mixture into a high shear machine for fiberization at a fiberization speed of 35000 rpm / min for a fiberization time of 5 minutes to obtain a positive electrode mixture; preheat the positive electrode mixture at a preheating temperature of 80°C for 40 minutes, and then enter a hot press roller machine for rolling at a rolling pressure of 20t to roll the positive electrode mixture to obtain a positive electrode active material layer; the compaction density of the positive electrode active material layer is 3.5g / cm 3 , with a thickness of 350μm; the positive electrode preparation material is composed of 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture is composed of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene;

[0040] The graphite and the conductive carbon black were mixed, and the mixture was ball-milled at a speed of 500 rpm for 2 hours to obtain a negative electrode preparatory material; the negative electrode preparatory material was mixed with polytetrafluoroethylene, and the mixed mixture was placed in a high shear machine for fiberization at a fiberization speed of 35000 rpm / min and a fiberization time of 5 minutes to obtain a negative electrode mixture; the negative electrode mixture was preheated at a preheating temperature of 60°C for 30 minutes, and then rolled in a hot press roller machine at a rolling pressure of 12 tons to obtain a negative electrode active material layer; the compaction density of the negative electrode active material layer was 1.7 g / cm 3 , with a thickness of 180μm; the contents of the components of the negative electrode mixture are: by mass fraction, 99wt% graphite, 1wt% conductive carbon black, and the balance is polytetrafluoroethylene; the negative electrode preparatory material is composed of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture is composed of 99wt% negative electrode preparatory material and 1wt% polytetrafluoroethylene; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 6mm and a depth of 0.7mm;

[0041] Step 3: Mix polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer, stir and react at 150°C for 2 hours to obtain a modified polyolefin resin; mix the modified polyolefin resin, paraffin wax and conductive agent graphene, stir at a speed of 1200 rpm for 1.5 hours to obtain a conductive adhesive; the reaction mass ratio of polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer is 20:3:20; the reaction mass ratio of modified polyolefin resin, paraffin wax and conductive agent graphene is 10:1:10;

[0042] The conductive glue was respectively coated on the aluminum layer and the copper layer of the multi-layer current collector, and then the positive electrode active material layer was adhered to the aluminum layer and baked at 105°C for 15 minutes; then the negative electrode active material layer was adhered to the copper layer and baked at 100°C for 15 minutes to obtain a bipolar electrode; the thickness of the conductive glue was 1 μm.

[0043] Example 4: Compared with Example 3, the difference is that the negative electrode active material layer has no embossing design: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and an aluminum layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0044] Step 2: Mix nickel-cobalt-manganese 811, carbon nanotubes and conductive carbon black, and ball-mill at a speed of 500 rpm for 2 hours to obtain a positive electrode preparatory material; mix the positive electrode preparatory material and polytetrafluoroethylene, and put the mixed mixture into a high shear machine for fiberization at a fiberization speed of 35000 rpm / min for a fiberization time of 5 minutes to obtain a positive electrode mixture; preheat the positive electrode mixture at a preheating temperature of 80°C for 40 minutes, and then enter a hot press roller machine for rolling at a rolling pressure of 20t to roll the positive electrode mixture to obtain a positive electrode active material layer; the compaction density of the positive electrode active material layer is 3.5g / cm 3 , with a thickness of 350μm; the positive electrode preparation material is composed of 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture is composed of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene;

[0045] The graphite and the conductive carbon black were mixed, and the mixture was ball-milled at a speed of 500 rpm for 2 hours to obtain a negative electrode preparatory material; the negative electrode preparatory material was mixed with polytetrafluoroethylene, and the mixed mixture was placed in a high shear machine for fiberization at a fiberization speed of 35000 rpm / min and a fiberization time of 5 minutes to obtain a negative electrode mixture; the negative electrode mixture was preheated at a preheating temperature of 60°C for 30 minutes, and then rolled in a hot press roller machine at a rolling pressure of 12 tons to obtain a negative electrode active material layer; the compaction density of the negative electrode active material layer was 1.7 g / cm 3, with a thickness of 180μm; the contents of the components of the negative electrode mixture are: by mass fraction, 99wt% graphite, 1wt% conductive carbon black, and the balance is polytetrafluoroethylene; the negative electrode preparation is composed of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture is composed of 99wt% negative electrode preparation and 1wt% polytetrafluoroethylene;

[0046] Step 3: Mix polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer, stir and react at 150°C for 2 hours to obtain a modified polyolefin resin; mix the modified polyolefin resin, paraffin wax and conductive agent graphene, stir at a speed of 1200 rpm for 1.5 hours to obtain a conductive adhesive; the reaction mass ratio of polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer is 20:3:20; the reaction mass ratio of modified polyolefin resin, paraffin wax and conductive agent graphene is 10:1:10;

[0047] The conductive glue was respectively coated on the aluminum layer and the copper layer of the multi-layer current collector, and then the positive electrode active material layer was adhered to the aluminum layer and baked at 105°C for 15 minutes; then the negative electrode active material layer was adhered to the copper layer and baked at 100°C for 15 minutes to obtain a bipolar electrode; the thickness of the conductive glue was 1 μm.

[0048] Example 5: Compared with Example 3, the difference is that the positive and negative active material layers are not adhered to the multilayer current collector through the conductive glue, but only adhered to the current collector through the polytetrafluoroethylene binder in the positive and negative active material layers themselves: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and a copper layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0049] Step 2: Mix nickel-cobalt-manganese 811, carbon nanotubes and conductive carbon black, and ball-mill at a speed of 500 rpm for 2 hours to obtain a positive electrode preparatory material; mix the positive electrode preparatory material and polytetrafluoroethylene, and put the mixed mixture into a high shear machine for fiberization at a fiberization speed of 35000 rpm / min for a fiberization time of 5 minutes to obtain a positive electrode mixture; preheat the positive electrode mixture at a preheating temperature of 80°C for 40 minutes, and then enter a hot press roller machine for rolling at a rolling pressure of 20t to roll the positive electrode mixture to obtain a positive electrode active material layer; the compaction density of the positive electrode active material layer is 3.5g / cm 3 , with a thickness of 350μm; the positive electrode preparation material is composed of 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture is composed of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene;

[0050] The graphite and the conductive carbon black were mixed, and the mixture was ball-milled at a speed of 500 rpm for 2 hours to obtain a negative electrode preparatory material; the negative electrode preparatory material was mixed with polytetrafluoroethylene, and the mixed mixture was placed in a high shear machine for fiberization at a fiberization speed of 35000 rpm / min and a fiberization time of 5 minutes to obtain a negative electrode mixture; the negative electrode mixture was preheated at a preheating temperature of 60°C for 30 minutes, and then rolled in a hot press roller machine at a rolling pressure of 12 tons to obtain a negative electrode active material layer; the compaction density of the negative electrode active material layer was 1.7 g / cm 3 , with a thickness of 180μm; the contents of the components of the negative electrode mixture are: by mass fraction, 99wt% graphite, 1wt% conductive carbon black, and the balance is polytetrafluoroethylene; the negative electrode preparatory material is composed of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture is composed of 99wt% negative electrode preparatory material and 1wt% polytetrafluoroethylene; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 6mm and a depth of 0.7mm;

[0051] The positive electrode active material layer was directly bonded to the positive electrode side of the current collector and baked at 105° C. for 15 min. Then, the negative electrode active material layer was directly bonded to the negative electrode side of the current collector and baked at 100° C. for 15 min to obtain a bipolar electrode.

[0052] Example 6: The difference from Example 3 is that the negative electrode active material layer is firstly bonded to the multi-layer current collector and baked, and then the positive electrode active material layer is bonded to the multi-layer current collector and baked: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and a copper layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multi-layer current collector;

[0053] Step 2: Mix nickel-cobalt-manganese 811, carbon nanotubes and conductive carbon black, and ball-mill at a speed of 500 rpm for 2 hours to obtain a positive electrode preparatory material; mix the positive electrode preparatory material and polytetrafluoroethylene, and put the mixed mixture into a high shear machine for fiberization at a fiberization speed of 35000 rpm / min for a fiberization time of 5 minutes to obtain a positive electrode mixture; preheat the positive electrode mixture at a preheating temperature of 80°C for 40 minutes, and then enter a hot press roller machine for rolling at a rolling pressure of 20t to roll the positive electrode mixture to obtain a positive electrode active material layer; the compaction density of the positive electrode active material layer is 3.5g / cm 3 , with a thickness of 350μm; the positive electrode preparation material is composed of 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture is composed of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene;

[0054] The graphite and the conductive carbon black were mixed, and the mixture was ball-milled at a speed of 500 rpm for 2 hours to obtain a negative electrode preparatory material; the negative electrode preparatory material was mixed with polytetrafluoroethylene, and the mixed mixture was placed in a high shear machine for fiberization at a fiberization speed of 35000 rpm / min and a fiberization time of 5 minutes to obtain a negative electrode mixture; the negative electrode mixture was preheated at a preheating temperature of 60°C for 30 minutes, and then rolled in a hot press roller machine at a rolling pressure of 12 tons to obtain a negative electrode active material layer; the compaction density of the negative electrode active material layer was 1.7 g / cm 3 , with a thickness of 180μm; the contents of the components of the negative electrode mixture are: by mass fraction, 99wt% graphite, 1wt% conductive carbon black, and the balance is polytetrafluoroethylene; the negative electrode preparatory material is composed of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture is composed of 99wt% negative electrode preparatory material and 1wt% polytetrafluoroethylene; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 6mm and a depth of 0.7mm;

[0055] Step 3: Mix polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer, stir and react at 150°C for 2 hours to obtain a modified polyolefin resin; mix the modified polyolefin resin, paraffin wax and conductive agent graphene, stir at a speed of 1200 rpm for 1.5 hours to obtain a conductive adhesive; the reaction mass ratio of polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer is 20:3:20; the reaction mass ratio of modified polyolefin resin, paraffin wax and conductive agent graphene is 10:1:10;

[0056] The conductive glue was applied to both sides of the multilayer current collector respectively, and then the negative electrode active material layer was adhered to the positive electrode side and baked at 100°C for 15 minutes; then the positive electrode active material layer was adhered to the negative electrode side and baked at 105°C for 15 minutes to obtain a bipolar electrode; the thickness of the conductive glue was 1 μm.

[0057] Example 7: The difference from Example 1 is that the negative electrode active material layer and the positive electrode active material layer are simultaneously baked after being bonded to the multilayer current collector: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and a copper layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0058] Step 2: Mix nickel-cobalt-manganese 811, carbon nanotubes and conductive carbon black, and ball-mill at a speed of 500 rpm for 2 hours to obtain a positive electrode preparatory material; mix the positive electrode preparatory material and polytetrafluoroethylene, and put the mixed mixture into a high shear machine for fiberization at a fiberization speed of 35000 rpm / min for a fiberization time of 5 minutes to obtain a positive electrode mixture; preheat the positive electrode mixture at a preheating temperature of 80°C for 40 minutes, and then enter a hot press roller machine for rolling at a rolling pressure of 20t to roll the positive electrode mixture to obtain a positive electrode active material layer; the compaction density of the positive electrode active material layer is 3.5g / cm 3 , with a thickness of 350μm; the positive electrode preparation material is composed of 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture is composed of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene;

[0059] The graphite and the conductive carbon black were mixed, and the mixture was ball-milled at a speed of 500 rpm for 2 hours to obtain a negative electrode preparatory material; the negative electrode preparatory material was mixed with polytetrafluoroethylene, and the mixed mixture was placed in a high shear machine for fiberization at a fiberization speed of 35000 rpm / min and a fiberization time of 5 minutes to obtain a negative electrode mixture; the negative electrode mixture was preheated at a preheating temperature of 60°C for 30 minutes, and then rolled in a hot press roller machine at a rolling pressure of 12 tons to obtain a negative electrode active material layer; the compaction density of the negative electrode active material layer was 1.7 g / cm 3 , with a thickness of 180μm; the contents of the components of the negative electrode mixture are: by mass fraction, 99wt% graphite, 1wt% conductive carbon black, and the balance is polytetrafluoroethylene; the negative electrode preparatory material is composed of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture is composed of 99wt% negative electrode preparatory material and 1wt% polytetrafluoroethylene; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 6mm and a depth of 0.7mm;

[0060] Step 3: Mix polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer, stir and react at 150°C for 2 hours to obtain a modified polyolefin resin; mix the modified polyolefin resin, paraffin wax and conductive agent graphene, stir at a speed of 1200 rpm for 1.5 hours to obtain a conductive adhesive; the reaction mass ratio of polypropylene, maleic anhydride and styrene-ethylene-butylene-styrene block copolymer is 20:3:20; the reaction mass ratio of modified polyolefin resin, paraffin wax and conductive agent graphene is 10:1:10;

[0061] The conductive glue was coated on both sides of the multilayer current collector, and the positive and negative active material layers were adhered to the positive and negative sides respectively, and baked at 105°C for 15 minutes to obtain a bipolar electrode; the thickness of the conductive glue was 1 μm.

[0062] Comparative Example 1: Wet electrode preparation, the positive electrode side undergoes two rolling processes, and the rest is the same as Example 3, and the specific steps are as follows: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and an aluminum layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0063] Step 2: Mix nickel cobalt manganese 811, carbon nanotubes and conductive carbon black, and then add solvent N-methylpyrrolidone to dissolve to obtain positive electrode slurry; apply the positive electrode slurry to the multi-layer current collector aluminum layer, bake at 110°C for 15 minutes, and roll the dried positive electrode side and the current collector together to obtain a compaction density of 3.0g / cm 3 , a positive electrode active material preparatory layer with a thickness of 410 microns; the positive electrode slurry contains 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes, and 0.5wt% conductive carbon black; rolling parameters: rolling pressure is 80t;

[0064] Step 3: Mix artificial graphite, conductive carbon black and binder, and then add pure water as solvent to obtain negative electrode slurry; apply the negative electrode slurry to the multi-layer current collector copper layer, bake it for the second time at 100°C for 15 minutes, and roll the dried positive electrode side, current collector and negative electrode side together to obtain a compaction density of 3.3g / cm 3 , a positive electrode active material preparation layer with a thickness of 370 microns, and a compaction density of 1.65g / cm 3 , a negative electrode active material preparatory layer with a thickness of 190 microns, i.e., a bipolar electrode; the mass ratio of artificial graphite, conductive carbon black and binder is 95:1:4; the binder is a mixture of styrene-butadiene rubber and sodium carboxymethyl cellulose, with a mass ratio of 1:1; rolling parameters: the rolling pressure is 40t.

[0065] Comparative Example 2: Wet electrode production, rolling both sides at the same time, ensuring that the compaction density of the negative electrode side is 1.65g / cm 3 , the rest is the same as Example 3, and the specific steps are as follows: Step 1: a copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and an aluminum layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0066] Step 2: Mix nickel cobalt manganese 811, carbon nanotubes and conductive carbon black, and then add solvent N-methyl pyrrolidone to dissolve to obtain positive electrode slurry; mix artificial graphite, conductive carbon black and binder, and then add solvent pure water to obtain negative electrode slurry; the positive electrode slurry contains 98.5wt% nickel cobalt manganese 811, 1wt% carbon nanotubes, and 0.5wt% conductive carbon black; when preparing the negative electrode slurry, the mass ratio of artificial graphite, conductive carbon black and binder is 95:1:4; the binder is composed of a mixture of styrene butadiene rubber and sodium carboxymethyl cellulose, with a mass ratio of 1:1;

[0067] Step 3: Apply the positive electrode slurry to the multi-layer current collector aluminum layer and bake at 110°C for 15 minutes; apply the negative electrode slurry to the multi-layer current collector copper layer and bake it again at 100°C for 15 minutes; roll the dried positive electrode side, current collector and negative electrode side together to obtain a compaction density of 2.3g / cm 3 , a positive electrode active material preparation layer with a thickness of 430 microns, and a compaction density of 1.65g / cm 3 , a negative electrode active material preparatory layer with a thickness of 190 microns, that is, a bipolar electrode; rolling parameters: the rolling pressure is 40t.

[0068] Comparative Example 3: Wet electrode production, rolling both sides at the same time, ensuring that the compaction density of the positive electrode side is 3.3g / cm 3 , the rest is the same as Example 3, and the specific steps are as follows: Step 1: a copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and an aluminum layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0069] Step 2: Mix nickel cobalt manganese 811, carbon nanotubes and conductive carbon black, and then add solvent N-methyl pyrrolidone to dissolve to obtain positive electrode slurry; mix artificial graphite, conductive carbon black and binder, and then add solvent pure water to obtain negative electrode slurry; the positive electrode slurry contains 98.5wt% nickel cobalt manganese 811, 1wt% carbon nanotubes, and 0.5wt% conductive carbon black; when preparing the negative electrode slurry, the mass ratio of artificial graphite, conductive carbon black and binder is 95:1:4; the binder is composed of a mixture of styrene butadiene rubber and sodium carboxymethyl cellulose, with a mass ratio of 1:1;

[0070] Step 3: Apply the positive electrode slurry to the multi-layer current collector aluminum layer and bake at 110°C for 15 minutes; apply the negative electrode slurry to the multi-layer current collector copper layer and bake it again at 100°C for 15 minutes; roll the dried positive electrode side, current collector and negative electrode side together to obtain a compaction density of 3.3g / cm 3 , a positive electrode active material preparation layer with a thickness of 370 microns, and a compaction density of 1.9g / cm 3, a negative electrode active material preparatory layer with a thickness of 150 microns, that is, a bipolar electrode; rolling parameters: the rolling pressure is 100t.

[0071] Comparative Example 4: The difference from Comparative Example 1 is that the compaction density of the positive and negative electrode active material layers is greater: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and an aluminum layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0072] Step 2: Mix nickel cobalt manganese 811, carbon nanotubes and conductive carbon black, and then add solvent N-methylpyrrolidone to dissolve to obtain positive electrode slurry; apply the positive electrode slurry to the multi-layer current collector aluminum layer, bake at 110°C for 15 minutes, and roll the dried positive electrode side and the current collector together to obtain a compaction density of 3.7g / cm 3 , a positive electrode active material preparatory layer with a thickness of 330 microns; the positive electrode slurry contains 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes, and 0.5wt% conductive carbon black; rolling parameters: rolling pressure is 140t;

[0073] Step 3: Mix artificial graphite, conductive carbon black and binder, and then add pure water as solvent to obtain negative electrode slurry; apply the negative electrode slurry to the multi-layer current collector copper layer, bake it for the second time at 100°C for 15 minutes, and roll the dried positive electrode side, current collector and negative electrode side together to obtain a compaction density of 3.8g / cm 3 , a positive electrode active material preparation layer with a thickness of 320 microns, and a compaction density of 1.8g / cm 3 , a negative electrode active material preparatory layer with a thickness of 170 microns, i.e., a bipolar electrode; the mass ratio of artificial graphite, conductive carbon black and binder is 95:1:4; the binder is a mixture of styrene-butadiene rubber and sodium carboxymethyl cellulose, with a mass ratio of 1:1; rolling parameters: the rolling pressure is 60t.

[0074] Comparative Example 5: The difference from Comparative Example 1 is that the coating thickness of the positive and negative electrode active material layers is thicker: Step 1: A copper layer with a thickness of 1 μm is prepared on one side of a PET base film with a thickness of 6 μm by a magnetron sputtering process and a water electroplating process, and an aluminum layer with a thickness of 1 μm is prepared on the other side by a vapor deposition process to obtain a multilayer current collector;

[0075] Step 2: Mix nickel cobalt manganese 811, carbon nanotubes and conductive carbon black, and then add solvent N-methylpyrrolidone to dissolve to obtain positive electrode slurry; apply the positive electrode slurry to the multi-layer current collector aluminum layer, bake at 110°C for 15 minutes, and roll the dried positive electrode side and the current collector together to obtain a compaction density of 3.0g / cm 3, a positive electrode active material preparatory layer with a thickness of 440 microns; the positive electrode slurry contains 98.5wt% nickel-cobalt-manganese 811, 1wt% carbon nanotubes, and 0.5wt% conductive carbon black; rolling parameters: rolling pressure is 90t;

[0076] Step 3: Mix artificial graphite, conductive carbon black and binder, and then add pure water as solvent to obtain negative electrode slurry; apply the negative electrode slurry to the multi-layer current collector copper layer, bake it for the second time at 100°C for 15 minutes, and roll the dried positive electrode side, current collector and negative electrode side together to obtain a compaction density of 3.3g / cm 3 , a positive electrode active material preparation layer with a thickness of 420 microns, and a compaction density of 1.65g / cm 3 , a negative electrode active material preparatory layer with a thickness of 210 microns, i.e., a bipolar electrode; the mass ratio of artificial graphite, conductive carbon black and binder is 95:1:4; the binder is a mixture of styrene-butadiene rubber and sodium carboxymethyl cellulose, with a mass ratio of 1:1; rolling parameters: the rolling pressure is 70t.

[0077] Detection test:

[0078] Preparation of the battery: The bipolar electrodes of Examples 1-2 are stacked with a solid electrolyte to obtain a laminated battery cell; the laminated battery cell is loaded into a battery casing, and after packaging and formation, a solid-state battery is obtained. During the stacking process, the length and width of the diaphragm must exceed the negative electrode active material layer; the solid electrolyte is a lithium polyacrylate electrolyte. The bipolar electrodes of Examples 3-7 and Comparative Examples 1-5 are stacked and wound with a diaphragm to obtain a wound battery cell; the wound battery cell is loaded into a cylindrical casing, and after drying, an electrolyte is injected, and then packaged and formed to obtain a cylindrical battery. During the stacking process, the length and width of the diaphragm must exceed the negative electrode active material layer; the diaphragm is a polypropylene ceramic film; the electrolyte includes an electrolyte LiPF6 solution, an additive of vinylene carbonate, and a solvent of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate, and the volume ratio of each component of the solvent is 1:1:1.

[0079] Energy density test: before the cell is put into the shell, the diameter and height of the cell are measured, and its volume V0 is calculated, and then assembled to obtain a cylindrical battery. Under normal temperature, the battery prepared in the embodiment and comparative example is charged and discharged for the first time at a current of 0.33C. The charging is constant current and constant voltage charging, the end voltage is 4.2V, the end current is 0.05C, and the discharge end voltage is 2.5V. It is left for 12h; the constant current and constant voltage charging is performed at a current of 1C, the end voltage is 4.2V, and the end current is 0.05C; the discharge is performed at a current of 1C, and the discharge end voltage is 2.5V. The discharge capacity C0 of the cell is recorded, and the battery volume energy density = discharge capacity C0 / cell volume V0.

[0080] Cycle performance test: Under normal temperature environment, the batteries prepared in the embodiments and comparative examples are charged and discharged for the first time with a current of 0.33C, the charging is constant current and constant voltage charging, the termination voltage is 4.2V, the cut-off current is 0.05C, and the discharge termination voltage is 2.5V, and then the battery is left for 12h; constant current and constant voltage charging is performed with a current of 1C, the termination voltage is 4.2V, and the cut-off current is 0.05C, and the discharge is performed with a current of 1C, the discharge termination voltage is 2.5V, and the discharge capacity Cb of the battery cell during the first cycle is recorded; cycle life detection is performed with Cb as the battery capacity, the test conditions are under normal temperature conditions, 1C / 1C cycle, the voltage range is 2.5-4.2V, and it is left for 5min in the middle, and the discharge process capacity Ce is recorded during the cycle process, and the ratio of Ce to Cb is the capacity retention rate during the cycle process.

[0081] Internal resistance test: Under normal temperature environment, adjust the test object to 50% SOC, discharge at a current rate of 1C for 18 seconds, record the battery voltage U2 before discharge termination, current I and battery voltage U1 after battery voltage stabilizes, and calculate according to the formula R = (U2-U1) / I to obtain the DC internal resistance R.

[0082] Battery capacity test: Under normal temperature, the battery prepared in the embodiment and comparative example is charged and discharged for the first time at a current of 0.33C. The charging is constant current and constant voltage charging, the end voltage is 4.2V, the end current is 0.05C, and the discharge end voltage is 2.5V. Then the battery is left for 12h; the constant current and constant voltage charging is performed at a current of 1C, the end voltage is 4.2V, the end current is 0.05C, and the discharge is performed at a current of 1C, the discharge end voltage is 2.5V, and the discharge capacity Cb of the battery cell during the first cycle is recorded, where Cb is the battery capacity. The results are shown in the following table:

[0083]

[0084] Example 4: The negative electrode active material layer has no embossing design, and the pole piece curls during the cycle, resulting in poor contact between the positive and negative electrodes, increased internal resistance of the battery, and reduced cycle life.

[0085] Example 5: The positive and negative active material layers are not adhered to the current collector through the conductive adhesive, the adhesion is poor, the interface resistance is high, and there is a risk of detachment after long-term circulation.

[0086] Example 6: The compaction density of the negative electrode active material layer is usually lower than that of the positive electrode, and it is more prone to powder loss than the positive electrode. If the negative electrode active material is coated first and then baked, the negative electrode needs to be rolled once more, which increases the risk of powder loss. Local lithium deposition may occur in the battery, resulting in a decrease in capacity and cycle life.

[0087] Example 7: The positive and negative electrodes cannot be wet-coated at the same time. If one side is coated first without baking, the slurry on the coated side will stick to the roller seriously when coating the other side, resulting in the electrode being scrapped and unable to be produced.

[0088] Comparative Example 1: After the positive electrode is rolled twice, the bonding force between the positive electrode active material layer and the current collector decreases, the interface resistance increases, and the cycle performance is affected.

[0089] Comparative Example 2: The positive electrode compaction density is insufficient, the contact area between the positive electrode particles is small, and the conductivity is poor, which leads to an increase in the internal resistance of the battery and a more serious cycle attenuation.

[0090] Comparative Example 3: The compaction density on the negative electrode side is too large, the negative electrode active material layer seriously loses powder, the electrode is scrapped, and the battery cannot be manufactured.

[0091] Comparative Example 4: The positive electrode was rolled twice, and the positive electrode was compacted too much, resulting in large-scale shedding of the positive electrode active material layer and the current collector, the pole piece was scrapped, and a complete battery could not be prepared.

[0092] Comparative Example 5: The thickness of the positive and negative electrodes is too thick. During the rolling process of the positive and negative active material layers and the current collector, the elongation of the insulating layer in the middle of the multi-layer current collector is much greater than that of the pure metal current collector, which leads to a large stress difference between the inner and surface layers of the active material layer, causing cracks in the active material layer, poor conductivity, increased internal resistance of the battery, and more serious cycle attenuation.

[0093] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0094] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A bipolar electrode, characterized in that: It includes a multilayer current collector formed by a composite of multiple metal layers; a positive electrode active material layer and a negative electrode active material layer with a target compaction density are obtained by dry mixing and roller pressing respectively, the positive electrode active material layer is adhered to the positive electrode side of the multilayer current collector, and the negative electrode active material layer is adhered to the negative electrode side of the multilayer current collector.

2. A bipolar electrode according to claim 1, characterized in that: The metal layer is any one of a copper layer and an aluminum layer.

3. A bipolar electrode according to claim 1, characterized in that: An insulating layer or a carbon layer is sandwiched between the multiple metal layers.

4. A bipolar electrode according to claim 1, characterized in that: The compaction density of the positive electrode active material layer is 3.5-4.0 g / cm 3 The compaction density of the negative electrode active material layer is 1.7-2.0g / cm 3 .

5. A bipolar electrode according to claim 1, characterized in that: The thickness of the positive electrode active material layer is 300-400 μm; the thickness of the metal layer is 1.0-1.5 μm; the surface of the negative electrode active material layer is embossed to form a pit structure, and the parameters of the pit structure are: the pit is circular or quasi-circular, with a diameter of 2-10 mm and a depth of 0.1-1 mm.

6. A bipolar electrode according to claim 1, characterized in that: The preparation process of the positive electrode active material layer is as follows: nickel cobalt manganese, carbon nanotubes and conductive carbon black are mixed, and the positive electrode preparatory material is obtained after ball milling; the positive electrode preparatory material is mixed with polytetrafluoroethylene, and the positive electrode mixture is obtained after high-speed shearing and fiberization; the positive electrode mixture is rolled to obtain the positive electrode active material layer; the positive electrode high-speed shearing and fiberization parameters are: the fiberization speed is 30000-50000rpm / min, and the fiberization time is 2-10min; the positive electrode rolling parameters are: the positive electrode mixture is first preheated at 80-120°C for 10-60min, and then rolled, and the rolling pressure is 8-20t; The preparation process of the negative electrode active material layer is as follows: graphite and conductive carbon black are mixed, and the mixture is ball-milled to obtain a negative electrode preparatory material; the negative electrode preparatory material and polytetrafluoroethylene are mixed, and the mixture is subjected to high-speed shear fiberization to obtain a negative electrode mixture; the negative electrode mixture is rolled to obtain a negative electrode active material layer; negative electrode high-speed shear fiberization parameters: the fiberization speed is 30000-50000rpm / min, and the fiberization time is 2-10min; negative electrode rolling parameters: the negative electrode mixture is first preheated at 50-100°C for 10-60min, and then rolled, and the rolling pressure is 6-12t.

7. A bipolar electrode according to claim 6, characterized in that: The positive electrode preparation material consists of 98.5wt% nickel cobalt manganese, 1wt% carbon nanotubes and 0.5wt% conductive carbon black; the positive electrode mixture consists of 99wt% positive electrode preparation material and 1wt% polytetrafluoroethylene; the negative electrode preparation material consists of 99wt% graphite and 1wt% conductive carbon black; the negative electrode mixture consists of 99wt% negative electrode preparation material and 1wt% polytetrafluoroethylene.

8. The method for preparing the bipolar electrode according to any one of claims 1 to 7, characterized in that: The positive electrode raw material and the negative electrode raw material are dry-mixed respectively, and then subjected to fiberization and roller pressing to obtain the positive electrode active material layer and the negative electrode active material layer; then the conductive glue is coated on both sides of the multi-layer current collector respectively, and then the positive electrode active material layer and the negative electrode active material layer are adhered on both sides respectively to obtain a bipolar electrode.

9. The method for preparing a bipolar electrode according to claim 8, characterized in that: The positive electrode active material layer is first bonded to the multi-layer current collector and then baked at 105-110° C. for 10-15 min. Then, the negative electrode active material layer is bonded to the multi-layer current collector and then baked at 100-105° C. for 10-15 min.

10. A battery prepared according to the bipolar electrode according to any one of claims 1 to 7.

Citation Information

Cited By

  • Battery monomer, pole piece, preparation method of pole piece, battery device and energy storage device

    CN120127102A